Hereditary Spastic Paraplegia and Intellectual Disability: Clinicogenetic Lessons From a Family Suggesting a Dual Genetics Diagnosis - Aguilera-Albesa, Sergio; de la Hoz, Ana Belén; Ibarluzea, Nekane; Ordóñez-Castillo, Andrés R.; Busto-Crespo, Olivia; Villate, Olatz; Ibiricu-Yanguas, María Asunción; Yoldi-Petri, María E.; García de Gurtubay, Iñaki; Perez de Nanclares, Guiomar; Pereda, Arrate; Tejada, María Isabel (Frontiers in Neurology, 2020)
Hereditary spastic paraplegias (HSPs) are a heterogeneous group of genetic disorders with spastic paraparesis as the main clinical feature. Complex forms may co-occur with other motor, sensory and cognitive impairment. A growing number of loci and genes are being identified, but still more than 50% of patients remain without molecular diagnosis. We present a Spanish family with autosomal dominant HSP and intellectual disability (ID) in which we found a possible dual genetic diagnosis with incomplete penetrance and variable expressivity in the parents and three siblings: a heterozygous duplication of 15q11.2-q13.1 found by arrays CGH and a novel missense heterozygous change in REEP1 (c.73A>G; p.(Lys25Glu) found by whole exome sequencing (WES). Following the standard genetic diagnosis approach in ID, arrays CGH analysis were first performed in both brothers affected by spastic paraparesis and ID from school age, and a heterozygous duplication of 15q11.2-q13.1 was found. Subsequently, the duplication was also found in the healthy mother and in the sister, who presented attention deficit/hyperactivity disorder symptoms from school age and pes cavus with mild pyramidal signs at 22 years of age. Methylation analysis revealed that the three siblings carried the duplication unmethylated in the maternal allele whereas their mother harbored it methylated in her paternal allele. Functional studies revealed an overexpression of UBE3A and ATP10A in the three siblings and the slightest cognitive phenotype of the sister seems to be related to a lower expression of ATP10A. Later, searching for the cause of HSP, WES was performed revealing the missense heterozygous variant in REEP1 in all three siblings and the father, who presented subtle pyramidal signs in lower limbs as well as the sister. Our findings reinforce the association of maternally-derived UBE3A overexpression with neurodevelopmental disorders and support that a spectrum of clinical severity is present within families. They also reveal that a dual genetic diagnosis is possible in patients with presumed complex forms of HSP and cognitive impairment.